CHALLENGES OF PLANNING FACILITIES FOR DIFFABLE PEOPLE IN PUBLIC BUILDINGS - elmiarti febriana; I Gede Oka Sindhu Pribadi (International Journal on Livable Space, 2020)
WHO and ILO found that access facilities for diffable people in developing countries have only reached 20-30 percent, while globally, it reaches 650 million people. The contribution of planners and construction service providers in efforts to facilitate access for diffable persons to public services has not been realized in the field because the builders still consider the provision of facilities to be a burden, causing a reduction in information and understanding of appropriate public facilities for them. It causes many public buildings to be considered insensitive to the needs of groups of diffable people. Therefore, it is essential to discuss the challenges faced in planning facilities for diffable persons to formulate strategic steps to overcome the challenges. This study aims to determine the considerations and constraints encountered during the implementation and planning stages of the facilities for diffable people. The method was a descriptive qualitative method to obtain a conceptual model regarding the considerations and recommendations for planning the facilities for diffable people.